Terrorist Acts as "Armed Attack": The Right to Self-Defense, Article 51(1/2) of the UN Charter, and International Terrorism - Stahn, Carsten (Tufts Archival Research Center, 2005)
Volume 27, Issue 2. Summer/Fall The U.S. administration's recent expansive interpretation of the right to self-defense under Article 51 of the UN Charter requires a concurrent reassessment of the legal concepts of necessity and proportionality in the context of terror.